Resistance of round tomato genotypes with determinate growth habit to two-spotted spider mites and silverleaf whitefly (Bioagro, 2020)
The requirement for round tomato hybrids, with determinate growth habit, for consumption in natura has considerably increased in Brazil. Despite all potential, tomato cropping presents as main obstacle the occurrence of pests during its cycle. The wild species Solanum pennellii has been used in order to obtain resistant genotypes. However, little research has been conducted to date aiming at developing round tomato genotypes that are resistant to pests and present determinate growth habit. Therefore, the experiment aimed at selecting determinate genotypes that are rich in acylsugars and at checking their levels of resistance to two of the most important pests of the crop (two-spotted spider mite and silverleaf whitefly). Thirteen treatments were evaluated, 10 UFU057-F2BC1 generations, and three check treatments that comprised the wild species S. pennellii and two cultivated tomatoes (cv. Santa Clara and UFU057). The genotypes UFU057-F2BC1#112 and UFU057-F2BC1#101 stood out, showing the highest acylsugar content (17.1 and 18.4 nmols·cm-2 of leaf area, respectively). The same genotypes presented an elevated level of resistance to Bemisia tabaci with low values of oviposition, number of nymphs and adults of the fly. Regarding the two-spotted spider mite, the genotype UFU057-F2BC1#112 did not allow much advance of the mites along the surface of the leaflet, thus, it is concluded that this genotype with determined growth habit is promising for the tomato genetic breeding program, presenting high acylsugar contents and moderate to elevated level of resistance to Tetranychus urticae and Bemisia tabaci.
Keywords: Allelochemicals; arthropod pests; Bemisia tabaci; biotic stress; Tetranychus urticae